Mapping of Landslide Prone Areas in Seki Village South Galela District North Halmahera Regency (Agrikan Jurnal Agribisnis Perikanan, 2024)
Landslides often occur in Seki village. This study aims to mapping the level of landslide disaster vulnerability in Seki village, South Galela Distric. Mapping landslide-prone areas is a mitigation narrative and a reference for consideration of future regional development. This study uses the Slope Morphology method (SMORPH). Mapping using the slope tools for slope slopes and the curvature tools for slope shapes. Data analysis was carried out overlay of slope and slope shapes maps using ArcGIS 10.8 software to obtain a map of the landslide vulnerability in Seki village. Results of the research on the convex slope shape have the highest area compared to concave and flat forms, which is 1540.49 ha or 65.44%. Seki village area can be divided into two segments based on distribution of slope slopes. The slope of 0-8% dominates the central area to the northern region, the southern part is dominated by slopes of 8-15% and 15-25%. Landslide vulnerability in Seki village for the central to northern region is dominated by the very low category, the southern region is dominated by a low level of vulnerability. Level of medium and high landslide vulnerability is spread across the southern and northern regions. The distribution area of medium and high landslide vulnerability needs to be a serious concern, especially the village government and the people of Seki village.
Keywords: Landslides; Seki; Mapping; Mitigation